Kegiatan Penyuluhan Iman Dan Imunitas Pada Masa New Normal Di Desa Bukit Rata, Kabupaten Aceh Tamiang - Firdaus, Muhammad; Hanifah, Intan; Astuti, Leni (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Efforts to increase faith and immunity during the new normal covid-19 are very important for society. Some strategies that can be implemented are education about the prevention of covid-19, namely trough making educational posters about covid -19, making videos on how to make mask, getting used to washing hands properly, planting rhizome plants to increase immunity and providing, explanations for avoiding disease from a religiouse perspective. The purpose of this activity is to increase awareness and knowledge so that they can be protected from the dangers of the covid-19 pandemic in Bukit Rata Village, Kejuruan Muda district, Aceh Tamiang. In this activity the community is directly involved so that people can understand more quickly and realize the importance of preventing and protecting themselves from the dangers of covid-19. The method used is in the form of counseling. The results of this service show differences that lead to better things than before regarding public awareness of the dangers of covid-19 and a perspective of faith in dealing with covid-19.